1999
DOI: 10.1152/jappl.1999.87.6.2366
|View full text |Cite
|
Sign up to set email alerts
|

Errors in estimating lung liquid volume in fetal lambs when using radiolabeled serum albumin and blue dextran

Abstract: Fetal lung liquid volume is usually determined by using radio-iodinated serum albumin (RISA) or blue dextran (BD) as volume tracers. We tested the reliability of both tracers at 124 (G124) and 142 days of gestation (G142; term = G147) when the labels were employed simultaneously. We measured the proportion of label bound reversibly to the lung, or apparently lost from the lung compartment, by washing out the lung with saline and 5% albumin. At G124, volume estimates with the two labels were similar. At G142, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
0
13
1
Order By: Relevance
“…In general, our data suggest that BDD is an acceptable indicator for studying fluid movements in fetal lungs, in at least partial disagreement with Pfister et al (31). However, it is difficult to compare methods from different laboratories.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…In general, our data suggest that BDD is an acceptable indicator for studying fluid movements in fetal lungs, in at least partial disagreement with Pfister et al (31). However, it is difficult to compare methods from different laboratories.…”
Section: Discussioncontrasting
confidence: 45%
“…It has been suggested that volumes might be affected by an unexplained jump in optical density of lung liquid between the first, "blank" sample and later samples, a jump that slowly subsided over the next hours (31). The significance of this effect is difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of the FITC-moiety or adhesion to protein lining the vasculature. Similar changes in the concentrations of other indicators such as Evans blue and methylene blue have been observed and it has been suggested that reduction or protein binding by the endothelium is responsible for this phenomenon (1,5,6,16,20). The actual causes for small losses of Evans blue from the vasculature in some of these studies remain uncertain.…”
Section: Discussionmentioning
confidence: 57%